Whose `Special Treatment'? Heterosexism and the Problems with Liberalism - Brickell, Chris (Sexualities, 2001)
This article examines the circulation of heterosexist positions within several recent New Zealand media texts. It argues that a recent form of discourse engages liberal language and assumptions in ways that support the privileged position of heterosexuality and the marginalization of homosexuality. The examples given highlight not only the tenor of some recent representations of homosexuality, but also some problems within liberalism. Most notable of these are liberalism's individualism and its failure to recognize the systemic nature of hierarchical power relationships and the constituting of lesbian and gay subjectivities within these relationships. These problems allow liberalism to play an active part in processes of domination and subordination.
Keywords: 1900-1999; 1990-1999; 2000 à aujourd'hui; 2000-2009; LGBTQIA2+; approches et analyses; capitalisme; cours; discipline; discours médiatique; histoire; hétérosexisme; libéralisme; nouvelle-zélande; océanie; premier cycle; périodes historiques; rapports de domination; régions géographiques; sciences humaines; soc2014; sociologie; systèmes d'oppressions; thématiques; violences

Fashioning Sapphism: The origins of a modern English lesbian culture - Doan, Laura L.... (Between men - between women, 2001)
Le procès pour obscénité très médiatisé de The Well of Loneliness (1928) de Radclyffe Hall est généralement reconnu comme le moment de cristallisation dans la construction d'une culture lesbienne anglaise moderne visible, marquant un grand fossé entre l'innocence et la déviance, le privé et le public, la nouvelle femme et la femme moderne. Lesbienne. Pourtant, malgré un accord sans réserve sur l'importance de ce moment culturel, les études antérieures déforment souvent de manière réductrice notre lecture de la formation de l'identité lesbienne au début du XXe siècle, soit en négligeant d'examiner en détail les développements qui ont conduit à l'interdiction, soit en encadrant les événements dans un cadre trop large. un contexte élargi par rapport à d’autres phénomènes culturels. Fashioning Sapphism situe la romancière Radclyffe Hall et d'autres lesbiennes éminentes, dont la pionnière du maintien de l'ordre des femmes, Mary Allen, l'artiste Gluck et l'écrivaine Bryher, au sein de la modernité anglaise à travers les multiples sites du droit, de la sexologie, de la mode et de la représentation littéraire et visuelle. , retraçant ainsi l'émergence d'une sous-culture lesbienne anglaise moderne au cours des deux premières décennies du XXe siècle. S'appuyant sur de nouvelles recherches approfondies dans les archives, le livre interroge à nouveau une série de mythes longtemps acceptés sans aucun doute (et toujours en circulation) concernant, pour n'en citer que quelques-uns, l'ampleur de l'homophobie dans les années 1920, le déploiement stratégique de la sexologie contre les minorités sexuelles, et la rigidité de certains codes culturels pour désigner le lesbienisme dans la culture publique.
Keywords: 1900-1999; 1910-1919; 1920-1929; approches et analyses; europe; histoire et politique; hétérosexisme; identités LGBTQIA2+; lesbianisme; personnes lesbiennes; périodes historiques; royaume-uni; régions géographiques; sexisme; sexualité; systèmes d'oppressions; thématiques; violences

The female circumcision controversy: an anthropological perspective - Gruenbaum, Ellen (University of Pennsylvania Press, 2001)
To the Western eye, there is something jarringly incongruous, even shocking, about the image of a six-year-old girl being held down by loving relatives so that her genitals can be cut. Yet two million girls experience this each year. Most Westerners, upon learning of the practice of female circumcision, have responded with outrage; those committed to improving the status of women have gone beyond outrage to action by creating various programs for "eradicating" the practice. But few understand the real life complexities families face in deciding whether to follow the traditional practices or to take the risk of change. InThe Female Circumcision Controversy, Ellen Gruenbaum points out that Western outrage and Western efforts to stop genital mutilation often provoke a strong backlash from people in the countries where the practice is common. She looks at the validity of Western arguments against the practice. In doing so, she explores both outsider and insider perspectives on female circumcision, concentrating particularly on the complex attitudes of the individuals and groups who practice it and on indigenous efforts to end it. Gruenbaum finds that the criticisms of outsiders are frequently simplistic and fail to appreciate the diversity of cultural contexts, the complex meanings, and the conflicting responses to change. Drawing on over five years of fieldwork in Sudan, where the most severe forms of genital surgery are common, Gruenbaum shows that the practices of female circumcision are deeply embedded in Sudanese cultural traditions-in religious, moral, and aesthetic values, and in ideas about class, ethnicity, and gender. Her research illuminates both the resistance to and the acceptance of change. She shows that change is occurring as the result of economic and social developments, the influences of Islamic activists, the work of Sudanese health educators, and the efforts of educated African women. That does not mean that there is no role for outsiders, Gruenbaum asserts, and she offers suggestions for those who wish to help facilitate change. By presenting specific cultural contexts and human experiences with a deep knowledge of the tremendous variation of the practice and meaning of female circumcision, Gruenbaum provides an insightful analysis of the process of changing this complex, highly debated practice.
Keywords: afrique; anthropologie; approches et analyses; corps; cours; discipline; histoire et politique; justice sociale; point de vue situé; premier cycle; ressource en ligne; régions géographiques; santé; sciences humaines; sex2283; soudan; système colonial; systèmes d'oppressions; thématiques; violences

Le harem et l'Occident - Mernissi, Fatima (Albin Michel, 2001)
"En Occident, le harem est représenté comme un lieu de plaisir où s'ébattent des femmes nues et lascives, odalisques d'Ingres et de Matisse, Schéhérazade en version hollywoodienne. En Orient, le harem est au contraire le lieu de la réclusion des femmes qui ne rêvent que de s'en émanciper, en jouant de leur talent et de leur intelligence, qu'elles aient vécu au temps du khalife Haroun Al-Rachid ou dans le harem domestique des années 50 à Fès. Ces deux représentations du harem - l'une fantasmée, l'autre historique - dessinent une vision différente, troublante et inattendue, non seulement de "la femme idéale" mais aussi de la séduction, de l'érotisme et des rapports entre les sexes. "Décris-moi ton harem, je te dirai qui tu es", semble nous suggérer avec humour Fatema Mernissi, bien connue du public pour sa vision aussi pertinente qu'impertinente d'un monde arabe en pleine mutation. Le Harem et l'Occident : un fascinant voyage au coeur des harems, un face à face revigorant entre les cultures autant qu'une méditation sur le pouvoir de l'image et la perception de soi."--Quatrième de couverture.
Keywords: 1800-1899; 1900-1999; afrique; approches et analyses; cours; discipline; fantasme; féminisme arabe; féminisme islamique; histoire et politique; maghreb; maroc; premier cycle; périodes historiques; representation; régions géographiques; sciences humaines; sex2283; sexualité; sociologie; système colonial; systèmes d'oppressions; thématiques; violences

The Quest for Modern Manhood: Masculine Stereotypes, Peer Culture and the Social Significance of Homophobia - Plummer, David C. (Journal of Adolescence, 2001)
This paper explores the use of homophobic terms by boys and young men and the meanings they invoke when using them. Highly detailed interviews were conducted with young men from diverse backgrounds about their own experiences while growing up and their observations of schools, teachers, family and peers. Homophobia was found to be more than a simple prejudice against homosexuals. Homophobic terms like “poofter” and “faggot” have a rich developmental history and play a central role in adolescent male peer-group dynamics. Homophobic terms come into currency in primary school. When this happens, words like poofter and faggot rarely have sexual connotations. Nevertheless, far from being indiscriminate terms of abuse, these terms tap a complex array of meanings that are precisely mapped in peer cultures, and boys quickly learn to avoid homophobia and to use it decisively and with great impact against others. Significantly, this early, very powerful use of homophobic terms occurs prior to puberty, prior to adult sexual identity and prior to knowing much, if anything, about homosexuality. An effect of this sequence is that early homophobic experiences may well provide a key reference point for comprehending forthcoming adult sexual identity formation (gay or not) because powerful homophobic codes are learned first.
Keywords: 1900-1999; 1990-1999; LGBTQIA2+; approches et analyses; australie; cours; discipline; homophobie; hétérosexisme; masculinité; nouvelle-zélande; océanie; patriarcat; premier cycle; périodes historiques; régions géographiques; santé; sciences humaines; soc2014; sociologie; systèmes d'oppressions; thématiques; violences

Les femmes des Premières nations, la gouvernance et la loi sur les Indiens : recueil de rapports de recherche en matière de politique - Sayers, Judith F.; MacDonald, Kelly A.; Fiske, Jo-Anne; Newell, Melonie; George, Evelyn; Cornet, Wendy (2001)
Table de matières: Pour une participation équitable des femmes des Premières nations à la gestion des affaires publiques, Judith F. Sayers et Kelly A. MacDonald. Les femmes des Premières nations et la gouvernance : Étude sur les coutumes et les nouvelles pratiques chez les femmes de la Première nation de Lake Babine, Jo-Anne Fiske, Melonie Newell et Evelyn George. La gouvernance des Premières nations, la Loi sur les Indiens et les droits à l’égalité des femmes, Wendy Cornet.
Keywords: amériques; approches et analyses; canada; cours; discipline; droits des femmes*; droits des femmes* autochtones; féminisme autochtone; histoire et politique; inégalités; militance; pol4105; premier cycle; racisme; régions géographiques; science politique; science politique et droit; sciences humaines; sciences sociales; sexisme; système colonial; systèmes d'oppressions; thématiques; violences